Crop rotation and cultivation effects on Convolvulus arvensis population dynamics in small grain organic cropping systems - Hettinger, Kara; Miller, Zach; Hubbel, Kyrstan; Seipel, Tim (Frontiers in Agronomy, 2023)
Convolvulus arvensis L. Scop. (field bindweed) is a difficult weed to manage in organic cropping systems. Convolvulus arvensis suppression often requires intensive tillage and cultivation practices that have negative impacts on soil quality. To improve C. arvensis management in organic cropping systems, ten treatments were compared in an experiment in Corvallis, MT, USA. Cropping system treatments were created to represent a range of both crop competitiveness and tillage intensity. In each of the ten treatments, C. arvensis ramet density was counted annually to estimate changes in density and population growth rates. Differences in soil chemical and physical properties between treatments were assessed. The intensive tilled fallow had decreasing C. arvensis populations over the study interval. The grazed cover crop treatment had increasing C. arvensis populations over the entire study period. The remaining eight cropping system treatments - including organic alfalfa, conventional alfalfa, less intensive tilled-fallow, spring-tilled cover crop, rye-cover crop, reduced tillage, and wheat-cover crop treatments showed stable C. arvensis populations over time. Soil from the two tilled fallow treatments had significantly lower soil aggregate stability, indicating higher erosion potential. Organic and conventional alfalfa and intensive tillage kept C. arvensis abundance low, but intensive tillage significantly decreased soil stability. Our results suggest incorporating a perennial forage phase can be a successful and sustainable option for perennial weed management in organic wheat systems.